Gelehrte Lebensläufe Habitus, Identität und Wissen um 1500 - Trüter, Ingo (Universitätsverlag Göttingen, 2017)
Attend a university? Get married? Graduate? 500 years ago, young men saw themselves already confronted with these questions, however compared to our days, under different social circumstances. Johannes Eck (1486-1543), Johannes Kingsattler (1486-1534) and Willibald Pirckheimer (1470-1530) were part of a precarious generation since they had to find their social positions in a rapidly changing society. How did they become the men, they themselves represented in their "self-narratives" and that we know today? Ingo Trüter examines the conditions which enabled the protagonists of this study to attain certain positions in the field of learning without assuming a biographical telos. Based on multiple types of sources and following a micro-historical approach, the study draws an illustrative image of men of learning around the year 1500, ranging from philosophical questions in the Wegestreit to the learned men's furniture and interior fittings of their houses.